Development of Interactive Media for Learning the Pythagorean Theorem Based on Ethnomathematics in Mosque Architecture - Weni Sastika; Rusydi Ananda (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aims to develop interactive learning media for the Pythagorean Theorem based on ethnomathematics using the architecture of the Medan Grand Mosque as a learning context. This research is motivated by students' low interest and understanding in mathematics, especially in the Pythagorean Theorem material. The development method used is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The validation results indicate that the media obtained a highly feasible category, with an average score of 92.5% from media experts and 91% from material experts. The teacher and student responses were 88% and 79.95%, respectively, based on practical criteria. The effectiveness test through N-Gain obtained an average value of 0.520 (moderate category). These results suggest that interactive media based on ethnomathematics can enhance students' understanding of mathematical concepts and provide more engaging learning experiences by connecting the material to local culture.